The Quality of English Coursebook for Nursing Department Student (Based on Students’, Lecturers’, And Experts’ Perspective) - Qoriatur Rahma; Safnil Safnil; Arono Arono (JOALL (Journal of Applied Linguistics and Literature), 2017)
This research was aimed to find out  the students’, lecturers’, and experts’ perspective toward the quality of the English coursebook for nursing department students. This research was an evaluative study. The participants of this research were 3 experts, 3 lecturers and 80 nursing students. The instrument of this research was an evaluation checklist based on  Mc.Donough and Shaw’s criteria.  The findings of the research were (1) over eighty percent participants agreed that syllabus fulfills the criteria for quality a nursing coursebook; (2) over eighty percent participants agreed that the content area fulfills the criteria for quality a nursing coursebook; (3) over ninety percent participants agreed that layout and physical appearance fulfills the criteria for quality a nursing coursebook; (4) over eighty percent participants agreed that practicality  fulfills the criteria for quality a nursing coursebook; (5) over eighty percent participants agreed that language use  fulfills the criteria for quality a nursing coursebook.